CORT Program after use in the development of creative thinking for students of architecture - Sura Kassim Ameem (Iraqi Journal of Architecture and Planning)
"Meditator notes the reality of contemporary Arab architecture in general and Iraq in particular, the absence of systematic rules of the Organization, it has become theoretically and practically the scene of a mixture of perceptions and visions of ""individual"" case resulting from the intellectual, cultural and social conditions. The observation of the reality of architectural education and academic in general, manifested the need to review a comprehensive methodology at the level of principles and rules. So the idea of the research problem, which is summarized (the development of creative thinking skills among students in architecture using CORT) The aims of the research can be intensified through the provision of a methodology based on qualitative intermingling between planting principles and foundations of independent thinking in logical stages generation and configuration with space to allow a logical dialogue and free thinking. This is exemplified by using ""Court"" adopted and applied universally to increase the area of two groups thinking of expanding the field of cognition and interaction in the development of creative thinking skills among students of architecture."